Comparison of the Detection Rates of Different Diagnostic Methods for Primary Peripheral Lung Cancer - Sun, Lijuan; Qin, Chao; Fu, Qun; Hu, Shuangmin; Zhao, Wenfei; Li, Hongyun (Frontiers in Oncology, 2022)
Objective: The present study aims to compare the detection rates of different diagnostic methods for primary peripheral lung cancer (PPLC). Methods: The detection rate and patient information were collected from a total of 359 cases of PPLC or a suspected diagnosis of lung cancer; among these, 186 cases were simultaneously treated with fibreoptic bronchoscopy, brush inspection and flush inspection, and 173 cases underwent a computed tomography (CT)-guided percutaneous lung biopsy (PNB). The positive detection rates of the different methods were compared. Results: In the detection of peripheral lesions (diameter of <5 cm), the CT-PNB had the significantly highest detection rate, followed by the combined basic method (fibreoptic bronchoscopy + brushing + flushing). The independent use of the three basic sampling methods showed a significantly lower detection rate compared with the combined use. Conclusion: In the diagnosis of peripheral lung cancer, the CT-PNB had the best detection rate; hence, it could be used in clinical practice for the diagnosis of such lesions.